RANCANG BANGUN DAN MODIFIKASI MESIN PENEPUNG BERAS BERPENGGERAK MESIN SEPEDA MOTOR - Efriwandy Simbolon; Jimmy Charlos Panjaitan; Agung Rai Putri; Anthonov Marandof; Damai Juliaman Zega; Moh.Fikri Pomalingo (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2023)
The use of two-wheeled motorbikes as transportation has inspired researchers to increase their use as drivers for agricultural tools and machinery (machines). The machine that will be made is portable so that it can be used by farmers and community service providers to help with post-harvest activities. The type of motorbike used in this research is the Honda Megapro 155cc. This motorbike has a powerful maximum power of 13.3 HP. This research focuses on modifying rice flour machines using motorbikes. Although conventional rice flour machines have made a major contribution to rice processing efficiency, the adoption of motorbike drives brings a new dimension in terms of mobility and accessibility. This modification aims to increase the efficiency, competitiveness and availability of rice flouring machines, especially in rural and remote areas where access to conventional energy resources may be limited. The benefit of this research is to improve the community's economy, especially grater business actors, because with this innovation, business actors can carry out grinding anywhere and of course can move from one market to another and can even carry out grinding door to door. This research method includes planning, machine design, machine fabrication, testing. Based on the research results obtained, the prototype of this grinding/floating machine can function well as proven by good test results. The test results from this research showed that the average time for grinding 1kg rice was 7 minutes 53 seconds and the average fuel required to grind 1kg rice was 150 ml